Students' Ability To Use English By Introducing Themselves - Amirul, Bani; Rahmi, Devina Aulia; Sitepu, Fatimah Az-Zahra; Ramadhani, Nurainun; Marpaung, Ummu Nabila (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The ability to speak English is a very valuable skill. With good English speaking skills, a person can confidently introduce himself or others. The aim of this research is to determine students' ability to use English and fluency when introducing themselves. The method used in this research uses qualitative methods with interview design and documentation. This research involved 26 students in class 3 of Al Ittihadiyah elementary school. The results of this research show that there are some students who are fluent in using English by introducing themselves. However, there are also some students who are still not fluent in using English, lack vocabulary and lack self-confidence.